Analysis of cleanliness, health, safety, and environmental sustainability in Merapi disaster-prone tourist villages - Wijaya, Oktomi; Putra, Bayu Cahya Eka (Universitas Ahmad Dahlan, 2023)
Background: Covid-19 pandemic has brought enormous effect on tourism sector. Covid-19 transmission can be prevented by the implementation of cleanliness, health, safety, and environmental sustainability (CHSE) aspects. This study aims to analysis the implementation of CHSE based on the Indonesian National Standard No. 9042 of 2021 (Standar Nasional Indonesia No.9042 Tahun 2021). Method: This was a quantitative study with survey design executed using CHSE guidelines of the Indonesian National Standard No. 9042 of 2021. The research sample consisted of 68 tourist cottages which were selected using total sampling technique. The research instrument was CHSE checklist to measure the implementation of CHSE in the tourist cottages. Results: Results of the study showed that the implementation of CHSE in tourist cottages in three tourist villages of Nganggring, Tunggul Arum, and Penting Sari were categorized as low with the scores of 22.90% for management, 37.02% for human resources, and 27.46% for guest participation. Conclusion: CHSE implementation in three tourist villages of Nganggring, Tunggul Arum, and Penting Sari has not be done in maximum manner so that the scores for each of the indicators of management, human resources, and guest participation were categorized as low.